Envy is not innate : a new model of thinking - Polledri, Patricia (Karnac Books, 2012)
This book is a comprehensive revision of the notion of envy, suggesting that envy is not innate and proposing some fresh ideas about its relation to psychopathology. Its argument is that envy is not simply attributable to constitutional forces, as Melanie Klein proposed, but the outcome of a complex process that includes a disturbance in symbolic functioning. This is the first time a critical review has been undertaken in book from of this cornerstone of British psychoanalysis. As the concept of envy needs to be explored in the light of attachment theory, an important aim of this book is in bridging attachment theory and classic psychoanalytic understanding of severe psychopathology. It also offers, for the first time, not only a reconceptualisation of the notion of envy, but a working model of development which is highly relevant to clinical practice. This model incorporates recent findings from neuroscience, which indicate that environmental influences are of prime importance to infantile development, and that disturbed attachments result in anatomical, physiological and psychological developmental disturbances. The model will be particularly useful in furthering our understanding of the influence on later mental health of an infant’s healthy attachment to its mother. From direct clinical experience in the forensic field of psychotherapy, and general practice, the author describes how psychosis and criminal behaviour represent a fundamentally acute failure in the capacity for social interdependence and altruism in human nature that is taken for granted in the psychologically well.